Myokine mediated muscle-kidney crosstalk suppresses metabolic reprogramming and fibrosis in damaged kidneys - Peng, Hui; Wang, Qianqian; Lou, Tanqi; Qin, Jun; Jung, Sungyun; Shetty, Vivekananda; Li, Feng; Wang, Yanlin; Feng, Xin-hua; Mitch, William E.; Graham, Brett H.; Hu, Zhaoyong (Nature communications, 2017)
Kidney injury initiates metabolic reprogramming in tubule cells that contributes to the development of chronic kidney disease (CKD). Exercise has been associated with beneficial effects in patients with CKD. Here we show that the induction of a myokine, irisin, improves kidney energy metabolism and prevents kidney damage. In response to kidney injury, mice with muscle-specific PGC-1α overexpression (mPGC-1α) exhibit reduced kidney damage and fibrosis. Metabolomics analysis reveals increased ATP production and improved energy metabolism in injured kidneys from mPGC-1α mice. We identify irisin as a serum factor that mediates these metabolic effects during progressive kidney injury by inhibiting TGF-β type 1 receptor. Irisin depletion from serum blunts the induction of oxygen consumption rate observed in tubule cells treated with mPGC-1α serum. In mice, recombinant irisin administration attenuates kidney damage and fibrosis and improves kidney functions. We suggest that myokine-mediated muscle-kidney crosstalk can suppress metabolic reprograming and fibrogenesis during kidney disease. Progressive tubule cell damage results in defects in mitochondrial metabolism and exercise seems to be beneficial during chronic kidney disease. Here Peng et al. show that irisin, an exercise-induced myokine, improves kidney energy metabolism by inhibiting TGF-β type 1 receptors and ameliorates fibrosis.